REAL-TIME COMPUTER CONTROL OF A MODEL TURBO-ALTERNATOR. - Harley, R; Nattrass, H; Wimpey, D; Limebeer, D; Levy, D; Leibrandt, SR (IEEE, 1977)
This paper presents experimental results obtained from tests conducted on a model laboratory turboalternator system controlled by a mini-computer. The design of the real-time computer controller was based on linear regulator theory. The computer is used to control both the set point and the feedback signals under steady state as well as transient conditions. The transient performance of this computer based system is compared with that of a conventional analog control scheme.